A novel indoor approach of artificial soiling deposition: achieving desired soil density and uniformity - Issalih, Ashraf; King, Peter; Karim, Mounia (TIB Open Publishing, 2025)
This work introduces a new indoor method for the artificial soiling of solar reflectors, employing a closed-loop wind tunnel chamber to replicate controlled deposition methods in a laboratory setting. The experimental setup includes dispersing a constant dust amount and allows manipulation of deposition to examine the impact of airflow speeds (1, 3, and 4.5 m/s), dust concentration and various humidity levels. The results show significant improvements of artificial soiling deposition, leading to more uniform deposition on the mirror surfaces and allowing a repeatable test.
Keywords: 5109 Space Sciences; 51 Physical Sciences; 7 Affordable and Clean Energy; Artificial Soiling; Chamber; Deposition